Innovation as a Factor in Sustainable Development of Russia’s Agriculture - N. Semenova, Nadezhda; A. Ivanova, Irina; Busalova, Svetlana G. (International Journal of Criminology and Sociology, 2022)
Sustainable agriculture is an integral aspect of the sustainable development of a socio-economic system. In this regard, innovation is considered to be one of the leading factors ensuring the development of sustainable agricultural since it increases the efficiency and competitiveness of the industry in the domestic and foreign markets. This study presents a system of recursive equations characterizing the innovations occurring within agricultural organizations in the regions of the Russian Federation. Additionally, the study assesses the sustainability of agricultural development in Russia by calculating the integrated index of five components: economic, innovative, social, ecological, and institutional. Also, the authors built a regression model that estimates the influence of innovation on the sustainability of agricultural development in Russia.